A Mouse Model for Ocular Surface Staphylococcus aureus Infection. Issue 1 (2nd March 2017) - Zhang, Zhiyong; Abdel‐Razek, Osama; Wang, Guirong
Abstract : Creation of an appropriate animal model that accurately reflects the disease and host immune response to bacterial infection in humans is a major challenge in ocular‐surface infection research. For decades, mice have been the ideal small animal model for ocular‐surface infection research because of the availability and relatively low cost of various genetic backgrounds, targeted defects, and immunologic reagents. By employing different combinations of mouse and bacterial strains, murine infection models can be used to explore a complete picture of bacterial infection and innate immunity of the ocular surface. A murine model of Staphylococcus aureus infection under normal ocular circumstances is presented here as a convenient and tractable model system in which to study mammalian host responses to pathogens. © 2017 by John Wiley & Sons, Inc.